Regulatory and operational complexities of conducting a clinical treatment trial during an Ebola Virus Disease epidemic - Rojek, A; Dunning, J; Leliogdowicz, A; Castle, L; Van Lieshout, M; Carson, G; Sahr, F; Olliaro, P; Horby, P (Oxford University Press, 2017)
The first Phase II and III clinical trials for treatments for Ebola Virus Disease were conducted during the west Africa (2013-16) outbreak. We report the operational practicalities of conducting a phase II clinical trial of TKM-130803 to international standards during this outbreak.